Utilizing Generative AI to Counter Learner Groupthink by Introducing Controversy in Collaborative Problem-Based Learning Settings - Wiss, Andrew; Showstark, Mary; Dobbeck, Kyle; Pattershall-Geide, Jennifer; Zschaebitz, Elke; Joosten-Hagye, Dawn; Potter, Kirsten; Embry, Erin (Online Learning, 2025)
This article highlights the foundational challenge of rapid interprofessional student team formation and the potential challenges that groupthink poses for newly-formed teams participating in collaborative problem-based learning activities. This article describes a mixed-methods study that addresses groupthink by introducing a generative artificial intelligence-based agent (genAI agent) into the small group processes of student teams engaging in a session of a well-established virtual interprofessional education methodology. The integration of this novel genAI tool into each student team was an intentional pedagogical technique, introduced in response to the challenges that newly-formed student teams may encounter as they rapidly come together and potentially contend with the many factors that may contribute to a state of groupthink. This study’s findings regarding: student perceptions of the GenAI agent; its integration into their team processes; its influence on team discussion and outcomes; the influence of faculty facilitators on acceptance of the genAI agent; and findings regarding the introduction of controversial viewpoints by a genAI agent as a mechanism to counter groupthink, are reported and discussed alongside recommendations for further research and utilization of this instructional approach. Keywords: Generative AI Agents, Artificial Intelligence in Education, Team Based Learning, Problem Based Learning, Groupthink, Controversy, Learner Collaboration, Team Dynamics, Psychological Safety, Interprofessional Education, Health Professions Education